Structure and tectonic history of the foreland basins of southernmost South America - Ghiglione, Matias (2010)
The common elements and differences of the neighboring Austral (Magallanes), Malvinas and South Malvinas (South Falkland) sedimentary basins are described and analyzed. The tectonic history of these basins involves Triassic to Jurassic crustal stretching, an ensuing Early Cretaceous thermal subsidence in the retroarc, followed by a Late Cretaceous-Paleogene compressional phase, and a Neogene to present-day deactivation of the fold-thrust belt dominated by wrench deformation. A concomitant Late Cretaceous onset of the foreland phase in the three basins and an integrated history during the Late Cretaceous-Cenozoic are proposed. The main lower Paleocene-lower Eocene initial foredeep depocenters were bounding the basement domain and are now deformed into the thin-skinned fold-thrust belts. A few extensional depocenters developed in the Austral and Malvinas basins during late Paleocene-early Eocene times due to a temporary extensional regime resulting from an acceleration in the separation rate between South America and Antarctica preceding the initial opening of the Drake Passage. These extensional depocenters were superimposed to the previous distal foredeep depocenter, postdating the initiation of the foredeep phase and the onset of compressional deformation. Another pervasive set of normal faults of Paleocene to Recent age that can be recognized throughout the basins are interpreted to be a consequence of flexural bending of the lithosphere, in agreement with a previous study from South Malvinas basin. Contractional deformation was replaced by transpressive kinematics during the Oligocene due to a major tectonic plate reorganization. Presently, while the South Malvinas basin is dominated by the transpressive uplift of its active margin with minor sediment supply, the westward basins undergo localized development of pull-apart depocenters and transpressional uplift of previous structures. The effective elastic thickness of the lithosphere for different sections of each basin is calculated using a dynamic finite element numerical model that simulates the lithospheric response to advancing tectonic load with active sedimentation.